Add-on imeglimin versus metformin dose escalation regarding glycemic control in patients with type 2 diabetes treated with a dipeptidyl peptidase-4 inhibitor plus low-dose metformin: study protocol for a multicenter, prospective, randomized, open-label, parallel-group comparison study (MEGMI study). Issue 6 (15th November 2022) - Nomoto, Hiroshi; Takahashi, Akihiro; Nakamura, Akinobu; Kurihara, Hiroyoshi; Takeuchi, Jun; Nagai, So; Taneda, Shinji; Miya, Aika; Kameda, Hiraku; Cho, Kyu Yong; Miyoshi, Hideaki; Atsumi, Tatsuya
Abstract : Introduction: Imeglimin is a novel anti-hyperglycemic drug that improves both insulin resistance and insulin secretion. The effects of imeglimin on glycemic control were confirmed in phase III clinical trials, but little is known about its effectiveness in daily clinical practice settings, especially compared with metformin. Therefore, we aim to clarify the efficacy of imeglimin in patients with type 2 diabetes (T2D) being treated with a dipeptidyl peptidase-4 (DPP-4) inhibitor plus low-dose metformin. Research design and methods: This is a multicenter, randomized, prospective, open-label, parallel-group trial. Seventy participants with T2D treated with a DPP-4 inhibitor plus metformin (500–1000 mg/day) for more than 12 weeks and a glycated hemoglobin (HbA1c) level of 52–85 mmol/mol (7.0%–9.9%) will be randomized to receive add-on imeglimin 1000 mg two times per day or metformin dose escalation for 24 weeks. Biochemical analyses and physical assessments will be performed at baseline and at the end of the study, and adverse events will be recorded. The primary endpoint is the change in HbA1c after 24 weeks. The secondary endpoints comprise the changes in blood pressure, pulse rate, body weight, abdominal circumference, and other laboratory parameters; the relationship between improvements of biological parameters including glycemic control and patient background characteristics; and side effects. Results: This study will reveal new insights into the incorporation of imeglimin into the diabetes treatment strategy. Conclusions: This will be the first randomized controlled trial to compare the efficacy of adding imeglimin versus metformin dose escalation on glycemic control in patients with T2D. Trial registration number: jRCT1011220005.